Spiritual needs of hospitalized patients from nurses' viewpoints: a qualitative study - Mohsen Faseleh, Jahromi (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
Introduction: Understanding the spiritual needs of patients in different cultural and religious fields is of great importance. The present study was designed and implemented to determine the spiritual needs of Iranian patients, from the viewpoint of nurses. Materials and Methods: This qualitative research was conducted with 15 nurses working in 2018 in the Jahrom University of Medical Sciences in Fars province. The purposeful sampling with a profound semi-structured interview was done. Results: The data analysis was done with the proposed Lundman & Graneheim steps. The six themes including "expressing beliefs", "attention to worship", "compliance with prohibitions", "being protected", "being respected" and "paying attention to rites of throes of death and death" were identified as the main spiritual needs of hospitalized patients. Conclusion: The spiritual needs of patients from the viewpoint of Iranian nurses are largely similar to the spiritual needs of other communities and cultures, with the difference that they, like other Iranians and Muslims, do not differentiate between spirituality and religion and offer all spiritual needs in the form of religious beliefs. And, they believe that despite the importance of the issue of spirituality among nurses and patients, the recognition of spiritual needs and the consistent provision of spiritual care in Iranian hospitals has not yet been institutionalized.